Novel approach to enhance the efficiency of mortar against radiations by co-incorporation of lead and boron compounds with calcium chloride - Hussein Al-kroom; Ahmed S. Ouda; Wageeh Ramadan; Mahmoud Gharieb; Mudar Hamsho; Hamdy A. Abdel-Gawwad (Scientific Reports)
Abstract Fabrication of heavy density mortar using aggregates reinforced with available solid inorganic chemical additives is of a great importance as a protective layer to mitigate radiations in nuclear facilities. The effect of lead oxide and borax decahydrate on the hydration kinetics was evaluated by determining setting time, leachability and compressive strength. To speed up the reaction, 0.5% calcium chloride was added to all formulations, and then the results were compared to their blank counterparts. Once, the optimal compositions were explored, another batch of mortar were designed to increase efficiency against radioactive sources with different photon energies. After 28 days, bulk density, linear attenuation coefficient, half-value layer, tenth-value layer, and mean-free path in the field of 137Cs and51Co were considered. Similarly, macroscopic effective removal cross-section was evaluated using radioactive source-239Pu-α-9Be. According to the previous literature, adding 0.2% PbO to cement is the optimal ratio without affecting hydration kinetics and phase composition. The study explored that, co-incorporation of PbO with 0.5% CaCl2 increases the ratio to 2.5%, while enhancing physico-mechanical and radiological characteristics against radioactive sources. Also, formulation incorporating 0.5% borax with 0.5% CaCl2 had superior attenuation against neutrons compared to other competitors.